EKSPLORASI ETNOMATEMATIKA PADA BENTUK DAN MOTIF ANYAMAN TIKEW BUDAYA LAMPUNG - Julia, Sintia; Andriani, Siska; Purwanti Nasution, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to reveal ethnomathematical elements in the forms and motifs of Tikew weaving as a traditional craft of the community in Desa Gedung Ratu, which has received limited scholarly attention, in the context of students’ low mathematics achievement and the prevailing perception of mathematics as abstract and monotonous. This research employed a qualitative approach using an ethnographic method through observation, interviews, and documentation, and the data were analyzed using an interactive model analysis consisting of data reduction, data display, and conclusion drawing. The findings indicate that the forms and motifs of Tikew weaving contain ethnomathematical elements in the form of plane geometry, solid geometry, and geometric transformations, including translation, reflection, and dilation, which naturally emerge through the arrangement of shapes and the repetition of motifs.